Love Letters. Issue 1 (1st May 2014) - Stanton, Graham
Abstract The task of identifying and reporting on the achievement of personal and ministerial formation at Youthworks College in Sydney, Australia was pursued through the use of letters composed collaboratively by teaching and supervising staff, addressed and delivered personally to students at the end of each teaching year. The content and process of letters provided to students is reviewed, leading to the identification of a loving disposition toward students from ministry educators as the essential element in providing and reporting on a program of formation in youth ministry education.